Dipcadi janae-shrirangii (Asparagaceae), a new species from the lateritic plateaus of Konkan region of Maharashtra, India - Chandore, Arun Nivrutti; Borude, Devidas Bhausaheb; Bhalekar, Paresh Pandharinath; Madhav, Nilesh Appaso; Gosavi, Kumar Vinod Chhotupuri (Phytotaxa, 2021)
Dipcadi janae-shrirangii is described and illustrated as a new species from the lateritic plateaus of Konkan region of Maharashtra, India. The new species is allied to the D. concanense (Dalzell) Baker, but differ in its small flowers and perianth tube as long as the lobes. Coloured photographs, illustrations of new species and key to the Indian species of Dipcadi having shiny white flowers and brownish black seeds are provided to facilitate the identification.